An overview of Australian exercise and sport science degrees - Kittel, Aden; Stevens, Christopher J.; Lindsay, Riki; Spittle, Sharna; Spittle, Michael (Frontiers in Education, 2023)
Exercise and Sport Science (EXSS) is a common degree offered at Australian universities, yet there is no systematic overview of this multidisciplinary field of study. This study aimed to determine the broad curriculum content of Australian EXSS degrees by summarising the units offered, identify most commonly delivered content areas, and capture course information such as work-integrated learning (WIL) requirements and majors offered. Data was gathered through publicly available university course pages, with 30 EXSS courses included and only core units identified. The most common Australian EXSS units were ‘Exercise Physiology’, ‘Biomechanics’, ‘Research Methods and Data Analysis’, ‘Exercise Prescription and Delivery’, and ‘Exercise and Sport Psychology’. WIL requirements ranged from 140-300 hours per course, and five courses offered majors. This study provides an overview of Australian EXSS courses, with the focus on exercise-related components reflecting accreditation requirements. Future research should examine how these courses equip students for the multidisciplinary EXSS industry.